IMPROVING LANGUAGE POLITENESS OF DYAH GALIH AGUNG SENIOR AND JUNIOR HIGH SCHOOL STUDENTS - Rahmadsyah Rangkuti; Zulfan Zulfan (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
This article analyzes the strategy for language politeness of Dyah Galih Agung Senior and Junior High School students, Deli Serdang District, which is realized through the use of speech acts. Every speaker should have knowledge on language politeness. Pragmatically speaking, language politeness is related and realized in speech acts. Speakers should understand speech contexts of their utterance and meanings contained in it. Some utterances may hurt the listeners but with choosing and using proper dictions and applying politeness, it will not hurt the listeners. The data collected using observation and conversation method (Sudaryanto, 2017) and then analyzed using Searle’s speech act theory (1979) and Leech’s politeness principles (2014). The findings show that the students in Dyah Galih Agung Senior and Junior High School, Deli Serdang District, use assertive, directive, commissive, and expressive speech act. Regarding the strategy for language politeness, the students use direct speech act more than indirect one which is influenced by the close social relationship among them. The findings also show that the application of Leech’s politeness strategy (2014) is able to improve the students’ language politeness ability.